2009
DOI: 10.1038/nchembio.194
|View full text |Cite
|
Sign up to set email alerts
|

Redox-sensitive cysteines bridge p300/CBP-mediated acetylation and FoxO4 activity

Abstract: Cellular damage invoked by reactive oxygen species plays a key role in the pathobiology of cancer and aging. Forkhead box class O (FoxO) transcription factors are involved in various cellular processes including cell cycle regulation, apoptosis and resistance to reactive oxygen species, and studies in animal models have shown that these transcription factors are of vital importance in tumor suppression, stem cell maintenance and lifespan extension. Here we report that the activity of FoxO in human cells is dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
150
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(151 citation statements)
references
References 44 publications
1
150
0
Order By: Relevance
“…The dynamic resolution of the heterodimer complex is in turn regulated by Trx. This thioldependent regulation of FOXO was supported by both substitution of critical cysteine residues and treatment with NAC, which abrogated the p300-lysine interaction (20).…”
mentioning
confidence: 90%
“…The dynamic resolution of the heterodimer complex is in turn regulated by Trx. This thioldependent regulation of FOXO was supported by both substitution of critical cysteine residues and treatment with NAC, which abrogated the p300-lysine interaction (20).…”
mentioning
confidence: 90%
“…One of the major ways in which metabolism can affect signaling pathways is through alterations of ROS levels. In turn, ROS can directly react with various proteins, such as kinases, phosphatases or transcription factors, to alter processes that regulate cell cycle progression, apoptosis, quiescence or differentiation (Dansen et al, 2009;Guo et al, 2010b;Velu et al, 2007). Furthermore, ROS can also directly modify metabolic enzymes or proteins that participate in nutrient-sensing pathways to direct the metabolic flux (Anastasiou et al, 2011;Brunelle et al, 2005;Sarbassov and Sabatini, 2005).…”
Section: Ros In Stem Cell Metabolismmentioning
confidence: 99%
“…Oxidation of Cys in PTEN catalytic sites causes inactivation (Lee et al, 2002) Modulation of the PI3K/AKT pathway PTEN inactivation by NOX-generated ROS increases PI3K-AKT activation in NSCs (Le Belle et al, 2011) Sirtuins (SIRTs) Cys oxidation inhibits SIRT1 activity (Zee et al, 2010) SIRTs are NAD + -dependent deacetylases that modulates the activity of FOXO TFs (Brunet et al, 2004;Kobayashi et al, 2005;Daitoku et al, 2004;Motta et al, 2004;van der Horst et al, 2004) SIRT3 controls ROS levels during HSC ageing (Brown et al, 2013) FOXOs possess 5-10 reactive Cys; the FOXO4 signaling switch from cell cycle arrest to apoptosis is redox mediated (direct); redox modulation of PTEN and AKT impact FOXOs negatively or positively, respectively (indirect) (Dansen et al, 2009) Can regulate the transcription of antioxidant enzymes, such as SOD2, catalase and GPX1…”
Section: Box 1 Tools For Ros Detection and Their Limitationsmentioning
confidence: 99%
“…Co-precipitation analysis revealed that the acetyltransferase CBP/p300 binds the first 52 amino acids of the N-terminal region of FOXO3a (14). Interestingly, p300 also directly acetylates FOXO transcription factors at several conserved lysine residues, Lys-242, Lys-245, and Lys-262 of FOXO3a (15)(16)(17). However, p300-dependent acetylation has been shown to have a dual function in FOXO-mediated transcription; either it can attenuate FOXO transcriptional activity or it can promote the recruitment and assembly of the transcriptional machinery, increasing their DNA-binding ability and transcriptional activity (18,19).…”
Section: Introductionmentioning
confidence: 99%